New Urban Agenda in Asia-Pacific. Governance for Sustainable and Inclusive Cities. - (:unkn) unknown (Springer, 2020)
This book explores significant aspects of the New Urban Agenda in the Asia-Pacific region, and presents, from different contexts and perspectives, innovative interventions afoot for transforming the governance of 21st-century cities in two key areas: (i) urban planning and policy; and (ii) service delivery and social inclusion. Representing institutions across a wide geography, academic researchers and development practitioners from Asia, Australia, Europe, and North America have authored the chapters that lend the volume its distinctly diverse topical foci. Based on a wide range of cases and intriguing experiences, this collection is a uniquely valuable resource for everyone interested in the present and future of cities and urban regions in Asia-Pacific.
Keywords: Nachhaltige Stadtentwicklung; Urban Governance; Paradigmenwechsel; Megastadt; Stadt-Land-Beziehung; Regionale Zusammenarbeit; Sozialinfrastruktur; Technische Infrastruktur; Öffentliche Dienstleistung; Internationaler Vergleich; Fallstudie; New Urban Agenda